Association of Serum Neurofilament Light Chain With Inner Retinal Layer Thinning in Multiple Sclerosis. (16th August 2022) - Sotirchos, Elias S.; Vasileiou, Eleni S.; Filippatou, Angeliki G.; Fitzgerald, Kathryn C.; Smith, Matthew D.; Lord, Hannah-Noelle; Kalaitzidis, Grigorios; Lambe, Jeffrey; Duval, Anna; Prince, Jerry L.; Mowry, Ellen M.; Saidha, Shiv; et al.
Abstract : Background and Objectives: Serum neurofilament light chain (sNfL) and optical coherence tomography (OCT)–derived retinal measures (including peripapillary retinal nerve fiber layer [pRNFL] and macular ganglion cell layer/inner plexiform layer [GCIPL] thickness) have been proposed as biomarkers of neurodegeneration in multiple sclerosis (MS). However, studies evaluating the associations between sNfL and OCT-derived retinal measures in MS are limited. Methods: In this retrospective analysis of a longitudinal, observational, single-center cohort study, sNfL levels were measured in people with MS and healthy controls (HCs) using single molecule array. Participants with MS were followed with serial OCT for a median follow-up of 4.5 years. Eyes with optic neuritis (ON) within 6 months of baseline OCT or ON during follow-up were excluded. Age-normative cutoffs of sNfL were derived using the HC data, and MS participants with sNfL greater than the 97.5th percentile for age were classified as having elevated sNfL (sNfL-E). Analyses were performed with mixed-effects linear regression models and adjusted for age, sex, race, and history of ON. Results: A total of 130 HCs (age: 42.4 ± 14.2 years; 62% female) and 403 people with MS (age: 43.1 ± 12.0 years; 78% female) were included. Elevated sNfL levels were present at baseline in 80 participants with MS (19.9%). At baseline, sNfL-E participants had modestly lower pRNFL (−3.03 ± 1.50 μm; p = 0.044) and GCIPL thickness (−2.74 ± 1.02 μm; p = 0.007). As compared with those with sNfL within the reference range, eyes from NfL-E participants exhibited faster longitudinal thinning of the pRNFL (45% faster; −0.74 vs −0.51 μm/y; p = 0.015) and GCIPL (25% faster; −0.35 vs −0.28 μm/y; p = 0.021). Significant differences in rates of pRNFL and GCIPL thinning between sNfL groups were found only in those with relapsing-remitting MS but not progressive MS. Discussion: Elevated baseline sNfL is associated with accelerated rates of retinal neuroaxonal loss in relapsing-remitting MS, independent of overt ON, but may be less reflective of retinal neurodegeneration in progressive MS.